2021
DOI: 10.1039/d1nj00155h
|View full text |Cite
|
Sign up to set email alerts
|

Furil-based ionic small molecules for green-emitting non-doped LECs with improved color purity

Abstract: Two novel furil based small molecules FlBzPy and FlThPy were designed and synthesized with simple synthetic procedures for the first time for the LEC application. The optical, thermal, electronic, electroluminescent,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Electric measurements of single crystals of MV salts of the oxonium‐ and sulfonium‐type derivatives, exhibited a semiconducting behavior with very high conductivity at room temperature (10 −1 –10 −2 S cm −1 and 10 −2 –10 ‐3 S cm −1 , respectively). Finally, integrating the PTXTX‐based derivatives as emissive materials into LECs led to the first mid‐emitting devices with performances similar to the state‐of‐art small molecule‐based LECs [56,60,65,66,69,70] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electric measurements of single crystals of MV salts of the oxonium‐ and sulfonium‐type derivatives, exhibited a semiconducting behavior with very high conductivity at room temperature (10 −1 –10 −2 S cm −1 and 10 −2 –10 ‐3 S cm −1 , respectively). Finally, integrating the PTXTX‐based derivatives as emissive materials into LECs led to the first mid‐emitting devices with performances similar to the state‐of‐art small molecule‐based LECs [56,60,65,66,69,70] …”
Section: Discussionmentioning
confidence: 99%
“…emitting devices with performances similar to the state-of-art small molecule-based LECs. [56,60,65,66,69,70]…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…Therefore, we have analyzed the thermal stability of the materials by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). We have noticed excellent thermal stability for the emitter materials, and hence we can draw out the possibility of stability roll-off due to Joule heating …”
Section: Introductionmentioning
confidence: 85%
“…To date, thenil-based small molecules have not been used for the fabrication of LEC devices. It has been reported that heteroatoms containing small-molecule LEC devices are comparatively stable from others. , In the synthesis of small molecules for LEC application, researchers are now making use of alkyl chains for easy solution processability and carrier transport. , Moreover, the donor–acceptor systems in small-molecule LECs have widespread acceptance nowadays. Considering all these factors, we are reporting a D–A system comprising thenil as well as pyrene on to which an imidazolium ring is attached, which is tethered with an alkyl chain.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that heteroatoms containing small-molecule LEC devices are comparatively stable from others. 64,65 In the synthesis of small molecules for LEC application, researchers are now making use of alkyl chains for easy solution processability and carrier transport. 66,67 Moreover, the donor−acceptor systems in small-molecule LECs have widespread acceptance nowadays.…”
Section: Introductionmentioning
confidence: 99%